Looking at the Link between Parents’ Educational Backgrounds and Students’ English Achievement - LENNY MARZULINA; NOVA LINGGA PITALOKA; HERIZAL HERIZAL; MUHAMAD HOLANDYAH; DIAN ERLINA; INDAH TRI LESTARI (Indonesian Research Journal in Education |IRJE|, 2018)
This study investigated the link between parents’ educational background and students’ English achievement at one senior high school in Palembang, South Sumatra, Indonesia. One hundred and eight senior high school students were involved in this study. Data were collected through a parents’ educational background questionnaire and an English test. Descriptive statistics, Pearson product moment correlation, and regression analysis were employed to analyze the data. The results of the Pearson product moment correlation coefficient revealed that parents’ educational background significantly correlated with the students’ English achievement. Additionally, the results of the linear regression analysis indicated that there was a correlation between parents’ educational background and students’ English achievement. Although the contribution was small and there were other factors that contribute to the students’ academic achievement, parents’ educational background is important in supporting their children’s English achievement.